The impact of tax and transfer systems on children in the European Union - Miles Raymond Corak; Christine Lietz; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2005)
The objective of this paper is to analyse the impact of fiscal policy on the economic resources available to children, and on the child poverty rate. A static microsimulation model specifically designed for the purposes of comparative fiscal analysis in the European Union, EUROMOD, is used to study the age incidence of government taxes and transfers in 2001 in 15 EU countries. Three related questions are addressed. First, what priorities are currently embodied in government budgets across age groups, and in particular to what degree do cash transfer and tax systems benefit children relative to older groups? We find that in most countries children receive a higher proportion of their share of household income from government transfers than young and middle-aged adults, but this is not universally the case. Low income children receive 60 per cent to 80 per cent of their income from transfers in all countries with child poverty rates lower than 10 pr cent. But the proportion is much lower, 20 per cent to 30 per cent, in countries with higher child poverty rates. Further, in many high child poverty countries the low income population in their 50s receive a higher proportion of household disposable income from state transfers than those younger than 18. These results are based on the broadest possible measure of public resources for children, one influenced not only by government budgets but also by the number of coresident adults, transfer payments directed to them, and their labour market behaviour. For this reason we also examine only those payments from the state depending on the presence of children, and ask: what fraction of the needs of children is supported by elements of the tax and transfer systems directed explicitly to them? There is considerable cross-country variation in the fraction of the additional household needs arising from having children which is supported through government transfers. It is higher than 30 per cent in 10 out of the 15 countries we study, but in the neighbourhood of 20 per cent in others, and in some cases close to only 10 per cent. We also find that tax concessions are an important component in many countries and cannot be ignored in measuring public resources for children. Our third set of findings has to do with the relationship between the measures of public resources we calculate and child poverty: what impact do measures of public resources for children have on child poverty rates? We find that poverty rates would be much higher in all countries if there were no child contingent transfers being made. But countries with the lowest poverty rates are those in which children benefit a good deal from other transfers not necessarily directed to them. In some cases this is because of public support to working mothers and fathers, in others because of intra-household transfers from co-resident adults. In another set of countries with low poverty rates child contingent payments make a large contribution to child poverty reduction. These countries mainly make use of universal benefits and tax concessions. Though their systems are not particularly targeted on low income children they nevertheless perform well in protecting children from poverty. This is in contrast with countries targeting income to children in poverty, where levels of spending may be comparable but child poverty rates are higher.
Keywords: 330; Children; child poverty; fiscal policy; European Union; Armut; Kinder; Öffentlicher Transfer; EU-Staaten